Reducing the Cost of Tunnel Form RC Frames by Using the Genetic Algorithms (مجلة جامعة اللاذقية- سلسلة العلوم الهندسية, 2019)
Eight years of war have damaged too many residential buildings in Syria; following to the UN report in 2017; 69% of the total damage was in residential buildings. In addition, it is very important to construct new residential buildings to solve the problem of increased number of inhabitants in many regions due to war.  Therefore, it is important to search of modern methods of construction, which ensure the reducing of the cost and the time of construction. One of these possible methods is tunnel form. Tunnel form was very effective in many places were damaged by earthquakes. In addition, tunnel form is very effective in RC frames cost in cellular buildings; it reduces the time, and ensures the good quality of final surfaces which will have a positive effect on the finishing costs. This paper will discuss the using of genetic algorithms to improve the feasibility of using tunnel form to reconstruct damaged buildings or construct new suburbs. We will search of reducing the cost of tunnel forms RC frame materials (concrete and reinforcement bars). ثماني سنوات من الحرب كان لها أثرها السلبي على القطاع السكني في سورية، فوفقا لتقرير الأمم المتحدة عام 2017، كانت نسبة الأبنية السكنية المدمرة 69% من مجموع الدمار الكلي. وأيضا ظهرت الحاجة الملحة لتشييد أبنية سكنية جديدة في عدة مناطق نظرا للازدحام السكاني فيها بسبب ظروف الحرب والنزوح. لذا كان لابد من البحث عن طرق تشييد حديثة تضمن خفض كلفة وزمن التشييد. إحدى الطرق المطروحة لإعادة التشييد هي القالب النفقي والذي أثبت فعاليته في إعادة تشييد عدة مناطق تعرضت للتدمير بفعل الزلازل في بلدان مختلفة. ووفقا للدراسات السابقة يعتبر القالب النفقي فعال جدا من حيث الناحية الاقتصادية في حال استخدامه في المشاريع الخلوية المتكررة، أيضا فهو هو يخفض زمن التشييد إضافة إلى عامل جودة الأسطح الناتجة مما ينعكس إيجابا على كلفة الاكساءات. سيناقش هذا البحث استخدام الخوارزميات الجينية في زيادة جدوى استخدام القالب النفقي سواء أكان الاستخدام لإعادة الاعمار في المناطق المدمرة أو كان لتشييد ضواحي سكنية جديدة. سيتم البحث في تخفيض كلف مواد تشييد الهيكل البيتوني (بيتون وتسليح) لأبنية القالب النفقي وذلك بالاعتماد على خواص هذا القالب واستخدام الخوارزميات الجينية في تصميم عناصره.